An experimental and computational study of CO2 adsorption in the sodalite-type M-BTT (M = Cr, Mn, Fe, Cu) metal–organic frameworks featuring open metal sites. Issue 20 (3rd May 2018) - Asgari, Mehrdad; Jawahery, Sudi; Bloch, Eric D.; Hudson, Matthew R.; Flacau, Roxana; Vlaisavljevich, Bess; Long, Jeffrey R.; Brown, Craig M.; Queen, Wendy L.
Abstract : The work provides molecular level insight into the CO2 adsorption properties of an isostructural series of MOFs, known as M-BTT. Abstract : We present a comprehensive investigation of the CO2 adsorption properties of an isostructural series of metal–organic frameworks, M-BTT (M = Cr, Mn, Fe, Cu; BTT 3− = 1, 3, 5-benzenetristetrazolate), which exhibit a high density of open metal sites capable of polarizing and binding guest molecules. Coupling gas adsorption measurements with in situ neutron and X-ray diffraction experiments provides molecular-level insight into the adsorption process and enables rationalization of the observed adsorption isotherms. In particular, structural data confirms that the high initial isosteric heats of CO2 adsorption for the series are directly correlated with the presence of open metal sites and further reveals the positions and orientations of as many as three additional adsorption sites. Density functional theory calculations that include van der Waals dispersion corrections quantitatively support the observed structural features associated with the primary and secondary CO2 binding sites, including CO2 positions and orientations, as well as the experimentally determined isosteric heats of CO2 adsorption.